Implementation of the Teacher's Role as Educator and Librarian at SDN 21 Pasar Pandan Air Mati, Solok City - Oktafiadi, Putri; Nelisa, Malta (Scinary, 2024)
This study aims to identify and describe the role of teachers as educators and librarians at SDN 21 Pasar Pandan Air Mati, Solok City, in three aspects: first, their key role in the curriculum; second, as information specialists; and third, as managers of information services. This research is a qualitative study using a descriptive method. The sampling in this study was conducted using purposive sampling, involving three individuals: two teacher-librarians as the first and second informants, and one school principal as the third informant. Data collection was carried out through interviews. Data analysis techniques were conducted in three stages: data reduction, data presentation, and drawing conclusions. The results of this study indicate that: first, the key role in the curriculum has been implemented effectively. This is reflected in the collaboration between the principal and teachers to ensure that information literacy receives special attention within the curriculum. Second, the role of teacher-librarians as information specialists in the school facilitates and supports the provision of education using the library for library users. However, library management needs further development to enhance its efficiency for students at the school. Third, as managers of information services, teacher-librarians have not been highly effective in designing and implementing strategies for evaluating the school’s collection. This is partly due to budget constraints, which hinder efforts to meet the library’s needs effectively. While efforts to promote books and a culture of reading have started to show progress, they remain suboptimal. This is primarily because teachers’ main focus and responsibilities lie in their primary role as educators at the school.